2017
DOI: 10.4102/sajcd.v64i1.185
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of public primary school teachers regarding noise-induced hearing loss in South Africa

Abstract: BackgroundNoise-induced hearing loss (NIHL) is an increasingly growing problem in young children. This is attributed to recreational noise being the most common cause of this problem. In young children, hearing problems can delay language development and reduce academic achievements. South Africa, in particular, has limited information and protective measures regarding the conservation of hearing in school-aged children.ObjectivesThe main aim of the study was to determine the perception of primary school teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Unfortunately, limited knowledge currently exists on the views and knowledge of ECD practitioners on childhood hearing loss in LMICs. A recent study was conducted by Ehlert [17] in South Africa to determine the perceptions of primary school teachers regarding hearing loss. However this study focused on noise-induced hearing loss, revealing a need for hearing conservation programs in schools as well as training of teachers in order to be successful.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, limited knowledge currently exists on the views and knowledge of ECD practitioners on childhood hearing loss in LMICs. A recent study was conducted by Ehlert [17] in South Africa to determine the perceptions of primary school teachers regarding hearing loss. However this study focused on noise-induced hearing loss, revealing a need for hearing conservation programs in schools as well as training of teachers in order to be successful.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the power transformer noise may affect residents around in both physiological and psychological ways, interfering with basic activities such as sleep, rest, work, study, and communication [1,2], the noise emission levels are facing more stringent environmental noise standards [3]. Based on this, the theoretical method and practical measures about assessing power transformer noise levels and reducing the influence of noise has aroused general concern, which is especially noticed by the transformer manufacturers [4] and the operators of power grids [5].…”
Section: Introductionmentioning
confidence: 99%
“…Hearing loss is more common in men than women (Le et al 2017). The prevalence of NIHL in children and adolescents is increasing and impact on academic achievement (Martin et al 2006, Ehlert 2016. A study conducted in Iran on 1,500 Elementary School students showed that the prevalence of conductive hearing loss in boys was 8.8% and 7.1% in girls; this result was similar to sensorineural hearing loss of 1% in men and 0.7% in women (Absalan et al 2013).…”
Section: Discussionmentioning
confidence: 89%